0
$\begingroup$

We are asked to prove the following integral;

$\int_0^x(\int_0^tf(u) du) dt=\int_0^xf(u)(x-u)du$

I know that we have to use integration by parts which when we differentiate a function will help us use the fundamental theorem of calculus. I just don't know when and were to apply this.

Thanks in advance!

$\endgroup$
  • $\begingroup$ The first step: $\int_0^x(\int_0^tf(u)\mathrm{d}u)\mathrm{d}t=[t(\int_0^tf(u)\mathrm{d}u)]_0^x-\int_0^xt\mathrm{d}(\int_0^tf(u)\mathrm{d}u)$ $\endgroup$ – Yuta Apr 30 at 5:54
0
$\begingroup$

This is analogous to the summation

$\begin{array}\\ \sum_{i=0}^n \sum_{j=0}^i f(j) &=\sum_{j=0}^n \sum_{i=j}^n f(j)\\ &=\sum_{j=0}^n f(j)\sum_{i=j}^n 1\\ &=\sum_{j=0}^n f(j)(n-j+1)\\ \end{array} $

Here

$\begin{array}\\ \int_0^x(\int_0^tf(u) du) dt &=\int_0^x\int_u^xf(u) dt du\\ &=\int_0^xf(u)\int_u^x1 dt du\\ &=\int_0^xf(u)(x-u) du\\ \end{array} $

The change in the order of integration follows from the fact that $0 \le t \le x $ and $0 \le u \le t$ is the same as $0 \le u \le x$ and $u \le t \le x$.

$\endgroup$
  • $\begingroup$ I'm not quite sure what you are doing here. I haven't seen this summation before. $\endgroup$ – Artem Pulemotov Apr 30 at 6:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.